Color Stability of the Bulk-Fill Composite Resins with Different Thickness in Response to Coffee/Water Immersion - Sayna Shamszadeh; Seyedeh Mahsa Sheikh-Al-Eslamian; Elham Hasani; Ahmad Najafi Abrandabadi; Narges Panahandeh (International Journal of Dentistry)
We aimed to evaluate the color stability of bulk-fill and conventional composite resin with respect to thickness and storage media. Twenty specimens of a conventional composite resin (6 mm diameter and 2 mm thick) and 40 specimens of the bulk-fill Tetric EvoCeram composite resin at two different thicknesses (6 mm diameter and 2 mm thick or 4 mm thick, n=20) were prepared. The specimens were stored in distilled water during the study period (28 d). Half of the specimens were remained in distilled water and the other half were immersed in coffee solution 20 min/d and kept in distilled water between the cycles. Color changes (ΔE) were measured using the CIE L⁎a⁎b⁎ color space and a digital imaging system at 1, 7, 14, and 28 days of storage. Data were analyzed using Two-way ANOVA and Tukey’s HSD post hoc test (P<0.05). Composite resins showed significant increase in color changes by time (bulk-fill > conventional; P<0.001). Coffee exhibited significantly more staining susceptibility than that of distilled water (P<0.001). There was greater color changes with increasing the increment thickness, which was significant at 14 (P<0.001) and 28 d (P<0.01). Color change of bulk-fill composite resin was greater than that of the conventional one after coffee staining and is also a function of increment thicknesses.